2022
DOI: 10.1101/2022.02.24.22271474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current status and future opportunities in modeling Multiple Sclerosis clinical characteristics

Abstract: Development of effective treatments requires understanding of disease mechanisms. For diseases of the central nervous system (CNS), like Multiple sclerosis (MS), human pathology studies and animal models tend to identify candidate disease mechanisms. However, these studies cannot easily link identified processes to clinical outcomes, such as MS severity, required for causality assessment of candidate mechanisms. Technological advances now allow generation of thousands of biomarkers in living human subjects, de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We have observed that cross-validation generates broad range of results that encompass the effect sizes of the independent validation cohort, but the median of cross-validation results is still overly optimistic. This is consistent with our extensive observations using independent validation in all our projects (Boukhvalova et al, 2019; Liu et al, 2022; Masvekar et al, 2021; Messan et al, 2022; Pham et al, 2021). Therefore, while cross-validation should be included in all modeling studies, the independent validation must be considered a gold standard.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have observed that cross-validation generates broad range of results that encompass the effect sizes of the independent validation cohort, but the median of cross-validation results is still overly optimistic. This is consistent with our extensive observations using independent validation in all our projects (Boukhvalova et al, 2019; Liu et al, 2022; Masvekar et al, 2021; Messan et al, 2022; Pham et al, 2021). Therefore, while cross-validation should be included in all modeling studies, the independent validation must be considered a gold standard.…”
Section: Discussionsupporting
confidence: 92%
“…Thanks to a recent meta-analysis of 302 papers describing models of MS clinical outcomes (Liu et al, 2022), we can compare our results with other published MRI biomarker-based models. Using an associated website that allow users to dynamically explore this rich dataset, we identified 40 papers that used MRI biomarkers to model EDSS as ordinal scale and reported p-values, and 20 papers that reported effect sizes as R^2.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, our results are best interpreted in comparison to published literature. To do so, we recently published meta-analysis 45 of 302 publications that used clinical, imaging, or biomarker-based predictors of MS clinical outcomes: Table 2 of that meta-analysis summarizes studies predicting MS severity as continuous outcomes. The training cohorts' results explained maximum of 45% of variance, while independent validation cohorts explained maximum of 12% of variance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the meta-analysis of MS models (28), these are the strongest validated effect sizes for these 3 traditional outcomes used for regulatory approval of MS drugs, using any type of predictors (i.e., clinical/demographic, MRI, blood/CSF biomarkers or genes).…”
Section: Csf-biomarker Based Models Reliably Predict Traditional Ms O...mentioning
confidence: 99%